The Role of Sharia Fintech in Enhancing Financial Inclusion in the Digital Era - Alfian, Ian; Abd Majid, M Shabri; Sugianto (Journal of Finance and Islamic Banking, 2025)
Purpose: This study aims to critically examine the role of Sharia-compliant financial technology (fintech) in enhancing financial inclusion, particularly among underserved Muslim populations in the digital era. Method: Employing a Systematic Literature Review (SLR) guided by the PRISMA protocol, this study analyzes 20 peer-reviewed journal articles published between 2018 and 2025.. Results: The findings are organized into four thematic domains: (1) improved access to finance for MSMEs through Sharia fintech platforms, (2) the critical role of digital and Sharia financial literacy in building trust, (3) regulatory fragmentation and ecosystem limitations, and (4) the ethical imperative of embedding justice in Islamic financial inclusion. Implication: The study provides actionable policy recommendations for regulators, fintech developers, and Islamic financial institutions to foster a sustainable and ethically grounded digital finance ecosystem. Originality: This study contributes to the literature by combining Islamic financial inclusion theory with contemporary digital finance practices.